TDP-43 in Alzheimer’s disease is not associated with clinical FTLD or Parkinsonism - Jung, Youngsin (2014)
Widespread deposition of TAR DNA-binding protein of 43 kDa (TDP-43), a major protein inclusion commonly found in frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) can also be seen in a subset of cases with Alzheimer’s disease (AD). Some of these AD cases have TDP-43 immunoreactivity in basal ganglia (BG) and substantia nigra (SN), regions that when affected can be associated with parkinsonian signs or symptoms, or even features suggestive of frontotemporal dementia. Here, we examined the presence of clinical features of FTLD, parkinsonian signs and symptoms, and BG atrophy on MRI, in 51 pathologically confirmed AD cases (Braak neurofibrillary tangle stage IV–VI) with widespread TDP-43 deposition, with and without BG and SN involvement. All 51 cases had presented with progressive cognitive impairment with prominent memory deficits. None of the patients demonstrated early behavioral disinhibition, apathy, loss of empathy, stereotyped behavior, hyperorality, and/or executive deficits. Furthermore, TDP-43 deposition in BG or SN had no significant association with tremor (p = 0.80), rigidity (p = 0.19), bradykinesia (p = 0.19), and gait/postural instability (p = 0.39). Volumes of the BG structures were not associated with TDP-43 deposition in the BG. The present study demonstrates that TDP-43 deposition in pathologically confirmed AD cases is not associated with a clinical manifestation suggestive of FTLD, or parkinsonian features.